Historical Analysis of Prophet Muhammad’s Educational Methods in The Mecca and Medina Periods Based on Sirah Nabawiyah: Implications for Contemporary Islamic Education - Sabila Azmi Syahira; Iin Kandedes; Zaimudin (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to provide a historical analysis of the educational methods employed by the Prophet Muhammad (peace be upon him) during the Mecca and Medina periods, based on the Sirah Nabawiyah, and to explore their implications for the development of contemporary Islamic education. Employing a qualitative approach with a historical-descriptive method, the research examines primary sources in the form of classical works on the Sirah Nabawiyah and secondary sources consisting of contemporary academic studies published in reputable journals. The findings indicate that the Prophet’s educational method in Mecca focused on the formation of faith, moral character, and spiritual resilience through personal and dialogical approaches, particularly within the setting of Dar al-Arqam. In contrast, during the Medina period, the educational method evolved into a more systematic and institutional model, marked by the establishment of the mosque as the center of learning, the implementation of community-based instruction, and the integration of spiritual, social, and practical dimensions of education. The study further reveals that prophetic educational principles such as tadarruj (gradualism), hiwar (dialogue), qudwah (exemplary conduct), tarbiyah ruhiyah (spiritual cultivation), and ta‘lim ‘amali (practical learning) remain highly relevant in addressing the crises of contemporary Islamic education, which are characterized by the dichotomy of knowledge, moral decline, and detachment from spiritual values. The practical implications of this research include recommendations to integrate holistic approaches into Islamic educational curricula, to develop learning models grounded in exemplary conduct, and to build educational ecosystems that harmonize intellectual, spiritual, and social dimensions.